In-vitro study on prevalence of mycoflora in wheat seeds - Adhikari, P.; Khatri-Chhetri, G. B.; Shrestha, S. M.; Marahatta, S. (Journal of the Institute of Agriculture and Animal Science, 2018)
A study on incidence of mycoflora was carried out by blotter method in wheat seeds. Forty seed sample of wheat (Triticum aestivum) was collected, ten varieties/genotypes each from Chitwan; Kaski; Banke and Lalitpur. The study was done at Seed Quality Control Center, Hariharbhawan, Lalitpur, Nepal, during August to December, 2013, with the objective of determining fungi associated with wheat seeds in-vitro. A total of eighteen species of fungi within thirteen genera were detected. Alternaria alternata and Bipolaris sorokiniana were predominant in all the varieties/genotypes and locations. Percentage frequency and type of fungi detected varied with variety and location. Among all fungi, mean frequency (76.00%) and relative abundance (55.15%) were highest of Alternaria alternata. Among the seeds of different location, B. sorokiniana was found highest from the seed of Banke and A. alternata from seeds of Lalitpur. Lowest percentage frequency of fungi was found in genotype BL 4009 (3.06%) from Chitwan and in variety Nepal 297 (6.25%) from Kaski, and highest in genotype BL 1177 (16.40%) from Banke. Nepalese wheat seeds appeared prevailed with many pathogenic fungi. Therefore, selection of wheat seeds from resistant varieties and areas with lower temperature and relative humidity, and their treatment is suggested to reduce disease and increase yield. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, Page: 27-34